Local Evolution of Three-Dimensional Microstructure Morphology of Planar Anode-Supported SOFC. (2nd June 2015) - Brus, Grzegorz Adam; Iwai, Hiroshi; Otani, Yuki; Sciazko, Anna; Saito, Motohiro; Yoshida, Hideo; Szmyd, Janusz S.
Abstract : In this research a cell stack with standard power output 100 W was tested over the period of 3700 hours. After the long-term operation subsequent post-test analysis of anode microstructure has been conducted using combination of focused ion beam and scanning electron microscopy. Obtained data was reconstructed into three-dimensional images, based on which the microstructure parameters were obtained. The microstructure parameters were quantified at three different location in the selected cells; inlet, middle and outlet. The obtained results indicate strong microstructure morphology change after long operation time and revealed a non-homogeneous degradation behavior.